Sistem Informasi Survei Kepuasan Masyarakat pada Pelayanan Publik di Kabupaten Serdang Bedagai Berbasis Web - Hutagalung, Estri Aprilia; Siringoringo, Rimbun; Perangin-angin, Resianta (Universitas Methodist Indonesia, 2024)
Public services play an important role in real terms for the community as a form of service to the community. Certain community services can be facilities that support people's lives, such as roads, clean water, and other services. The higher the quality of public services, the better people's lives will be, meaning that there will be no problems that prevent them from carrying out their daily activities. Meanwhile, services are in the form of public services that are really needed by the community, such as health and education services as well as transportation arrangements. The quality of service at the Serdang Bedagai Regency Regent's Office is classified as